A paruterinid metacestode in the liver of a Neotropical bat (Molossus molossus) - Souza, Alex Junior Souza de (Elsevier, 2019)
We describe a case of microscopic liver lesion caused by larval cestode in a frugivorous bat (Molossus molossus) from the Western Brazilian Amazon. Histopathological analysis of liver indicated the occurrence of metacestode associated with multifocal histiocytic response and the phylogenetic analysis of Cox-I and 18S rDNA genes indicated that the parasite belonged to the family Paruterinidae. This is the first identification of cestodes of the family Paruterinidae in bats and may suggest a broad range of paruterinid tapeworm hosts to be investigated in the Brazilian Amazon.